Social Media Branding Strategy in StartUp Business - Arsiyanti Lestari; Siswantini Siswantini (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
Social media is an important tool in developing digital business. Therefore, it must be owned and utilized by every novice entrepreneur known as StartUp. There are so many things that can be employed through social media, including branding. The intense competition among startup entrepreneurs, who are fighting for sharing market in Jakarta, triggers to implement social media branding strategy. PickPack employs social media as one of marketing and communication channels to be able to create an engagement and brand awareness achievement. In branding, for example, if there is an accumulation of positive comments from certain brand users, it will not only increase brand awareness, but also raises the sales. Starting the process as startup business, it is necessary to build engagement with consumers. Thus, this study tries to examine what business strategies applied by startup business. Qualitative methodologies with a single case study method and reduction data analysis techniques were used in this study. Research located in PickPack Jakarta to analyze the strategy of social media branding. The results show that, first, processing social media branding must be in accordance with its role and selection of appropriate social networks thus increasing brand awareness. In using social media branding, the PickPack need to consider the interesting content that can be viral (widespread), so that brand awareness can be skyrocketed. Second, the message conveyed through the brand must be easily remembered by consumers. The message delivered must be different from other products and must have a relationship between brand and product category. Using taglines and interesting hashtag that help consumers easily search in internet making consumers keep PickPack brand in their mind. This means brand awareness can be strengthened by using a portent that fits the product category, and brand on social media branding. Doing repetition of the messages in same meaning with different contents can increase the memory of the brand and brand awareness going up. Keywords: brand, brand awareness, social media, social media branding, strategy